An Alternative Consensus Measure Based on the Gini Index for Group Decision-Making Problems - Del Moral, María José; Trillo, José Ramón; Pérez, Ignacio Javier; Tapia-García, Cristobal; Tapia, Juan Miguel (Journal of Advanced Computational Intelligence and Intelligent Informatics, 2025)
Measuring agreement among participants in group decision-making problems is critical to such processes. This paper introduces a novel consensus index derived from the Gini coefficient, which avoids the need for traditional aggregation matrices, simplifying calculations while maintaining robustness. The proposed Gini Consensus Index demonstrates properties of reciprocity and boundedness, making it a reliable alternative to traditional distance-based measures. Through a comparative statistical analysis using the Wilcoxon test, the GCI performed similarly to established methods but with computational advantages and enhanced stability. These features make it a promising tool for consensus evaluation in fuzzy preference frameworks.